CONSONANTS IN THE LANGUAGE BEING STUDIED - Sayfiddinova Mushtariybegim Faxriddin qizi (International Journal of Innovations in Engineering Research and Technology, 2021)
This article provides the readerswith the necessary information about consonants in the language being studied.